Review of the genus Anthonympha Moriuti, 1971 (Lepidoptera: Plutellidae) from China, with descriptions of four new species - Cong, Peixin; Fan, Ximei; Li, Houhun (Zootaxa, 2016)
Chinese species of Anthonmypha Moriuti are reviewd. Five species are recognized, four of which are described as new: Anthonympha truncata sp. nov., A. trapezia sp. nov., A. ligulacea sp. nov. and A. reniforma sp. nov. Images of adults and genitalia are provided, along with a key to distinguishing all the Chinese species.